2010
DOI: 10.1002/jcb.22637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of connective tissue growth factor/CCN2 expression in human dermal fibroblasts by interleukin‐1α and β

Abstract: Connective tissue growth factor (CTGF/CCN2) is a matricellular protein induced by transforming growth factor (TGF)-beta and intimately involved with tissue repair and overexpressed in various fibrotic conditions. We previously showed that keratinocytes in vitro downregulate TGF-beta-induced expression of CTGF in fibroblasts by an interleukin (IL)-1 alpha-dependent mechanism. Here, we investigated further the mechanisms of this downregulation by both IL-1alpha and beta. Human dermal fibroblasts and NIH 3T3 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…IL-1-mediated suppression of CTGF may thus indicate that IL-1 can suppress TGFβ signaling in our secretome. In support of this, opposing effects of IL-1 on tenascin-C and CTGF (similar to ours) have been reported [58]. Thrombospondin 1 (THBS-1) is an adhesive glycoprotein that mediates cell-to-cell and cell-to-matrix interactions.…”
Section: Resultssupporting
confidence: 87%
“…IL-1-mediated suppression of CTGF may thus indicate that IL-1 can suppress TGFβ signaling in our secretome. In support of this, opposing effects of IL-1 on tenascin-C and CTGF (similar to ours) have been reported [58]. Thrombospondin 1 (THBS-1) is an adhesive glycoprotein that mediates cell-to-cell and cell-to-matrix interactions.…”
Section: Resultssupporting
confidence: 87%
“…Interleukin-1 and -1 inhibit TGF--stimulated Smad3 phosphorylation by increasing Smad7 expression and by TGF-activated kinase1 (TAK1) 45) . Interfering with Smad3, PPAR and its ligands suppress CTGF expression in response to TGF- 46,47) .…”
Section: Runx2 Inhibits Tgf--induced Ctgf Expression By Interacting Wmentioning
confidence: 99%
“…CTGF is characteristically overexpressed in fibrotic diseases and stimulated by TGF‐β in dermal fibroblasts. We previously showed that IL‐1α counteract TGF‐β‐stimulated CTGF mRNA expression in fibroblasts [Nowinski et al, ]. In this study, using microarray, TGF‐β increased CTGF expression 15‐fold and IL‐1 inhibited this increase by 32% (q‐value = 0.06 for the latter).…”
Section: Discussionmentioning
confidence: 50%
“…One mechanism behind this may be keratinocyte‐mediated downregulation of TGF‐β in fibroblasts in a paracrine action [Le Poole and Boyce, ]. As another way to limit fibrosis, we previously identified IL‐1α secreted from keratinocytes as a mediator of CTGF mRNA and protein suppression in human dermal fibroblasts [Nowinski et al, ; Nowinski et al, ]. Since the skin has a unique reservoir of preformed IL‐1α in the epidermis, it is possible that this cytokine is an important player not only in the immune defense, but also to limit excessive scarring after injury [Murphy et al, ; Behm et al, ].…”
mentioning
confidence: 99%
See 1 more Smart Citation